Evaluasi Ketahanan Tanaman Padi Haploid Ganda Calon Tetua Padi Hibrida terhadap Wereng Batang Coklat dan Hawar Daun Bakteri - Iswari S. Dewi; A. Apriana; A. Sisharmini; Ida H. Somantri (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
The susceptibility of introduced hybrid rice to main rice pests and diseases is subject to be improved through the improvement of its parental lines, i.e. restorer and male sterile/cms lines. From previous experiment, through anther culture of F1 from maintainer or restorer crossed to released varieties we obtained doubled haploid spontaneous plants or pure lines. The objectives of this research were to evaluate those doubled haploid plants to brown plant hopper (BPH biotype SU) and bacterial leaf blight (BLB) strain IV and VIII. Standard Evaluation System for Rice (SES, IRRI) was used to evaluate their resistance to those pest and disease. Plant materials used were a) 15 doubled-haploid plants (DH2) potential as cms lines derived from anther culture of F1 IR58025B x Sintanur and IR62829B x Ciherang; and b) 17 doubled-haploid plants (DH2) potential as restorer lines derived from anther culture of F1 IR53942R x Ciherang and BR827-35R x Sintanur. Bioassay with BPH showed that for plants potential as maintainer lines there were only 3 moderately susceptible lines, while for plants potential as restorer lines there were one resistance line (BioR-Ac-W-HD-15) and one moderately resistance line (BioR-Ac-W-HD-16). The results of bioassay with BLB in lines potential as maintainer were: a). For BLB strain IV we obtained one moderately resistance line (BioM-Ac-W-HD-4), b) For BLB strain VIII we obtained 5 moderately resistance lines (BioM-Ac-W-HD-5, 6, 7, 11 dan 12). Furthermore, the results of bioassay with BLB in lines potential as restorer lines were: a) For BLB strain IV we obtained 2 moderately resistance lines (BioR-Ac-W-HD-15, and 16), b) For BLB strain VIII we obtained 16 moderately resistance lines, i.e. BioR-Ac-W-HD-(1, 2, 3, 4, 5, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, dan 17). All lines will be evaluated further in the field. Key words: doubled-haploid, rice, BPH, BLB